TECHNOLOGICAL FORECASTING AS CYCLIC SYSTEM - Victor M. Averbukh (Вестник Северо-Кавказского федерального университета, 2022)
The analysis of components of forecasting - from a task for development of the forecast before scheduling of reconstruction of production and a task for the following time log - proved recurrence of all process.